Kobiety w filozofii polskiej. Filozofowie polscy o kobietach - Kiejzik, Lilianna (1957- ) (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The book is devoted to the presence of women in the history of Polish philosophy and to the views of Polish philosophers on women, education, and emancipation. The author presents profiles of the first Polish women associated with philosophy, science, and social activity, analysing their intellectual achievements and their role in the social transformations of the nineteenth and twentieth centuries. The publication also discusses the evolution of perceptions of women in Polish philosophical and academic culture.
Keywords: kobiety w filozofii; filozofia polska; historia filozofii; feminizm; edukacja kobiet; emancypacja; filozofki polskie; historia kobiet; women in philosophy; Polish philosophy; history of philosophy; feminism; women`s education; emancipation; Polish women philosophers; women`s history